An Explorative Analysis of Using LMS (Lentera) in Writing Class at UIN Alauddin During Covid-19 - Aminah Aminah; Hardiani Ardin; Siska Angraini (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research aimed at finding out the students’ barriers in writing class and the advantages of using LENTERA as the LMS platform of Islamic State University (UIN) Alauddin Makassar in writing class during Covid-19 pandemic. This research employed a qualitative method with 9 participants from English and Literature Department students. The data were collected by using in-depth interview and documentation, then it was analyzed by using Miles and Huberman theory. The results of this research showed that English and Literature students who learned writing courses by using LENTERA application had several barriers such as network problems, difficulty in understanding the lesson, and inaccessible application. In addition, the advantages encountered by English and Literature students in writing course by using LENTERA application were facilitating the process of teaching and learning, facilitating the students in submitting the assignment, and providing accessible file storage. The researchers recommended that LENTERA features should be enhanced and the teachers should organize the material in attractive way so that during the teaching process the barriers can be reduced.